2021
DOI: 10.3390/rs13163284
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Multi-Sensors Data for Species Distribution Mapping Using Deep Learning and Envelope Models

Abstract: The integration of ecological and atmospheric characteristics for biodiversity management is fundamental for long-term ecosystem conservation and drafting forest management strategies, especially in the current era of climate change. The explicit modelling of regional ecological responses and their impact on individual species is a significant prerequisite for any adaptation strategy. The present study focuses on predicting the regional distribution of Rhododendron arboreum, a medicinal plant species found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…As any ML-derived product, our predictions would benefit from having more and better quality data on tree species, in particular those that come from NFI plots: it is now crucial to have such data freely available to monitor processes such as species compositional changes, niche shifts, forest regrowth and degradation, as recently stated by Nabuurs et al (2022) . Exploring more sophisticated and different ML algorithms such as Deep Learning (DL) techniques ( Lakshminarayanan, Pritzel & Blundell, 2016 ) for our ensemble framework is also another area of improvement given the wide variety of applications these methods possess and the results obtained in comparison with other conventional ML algorithms ( Choe, Chi & Thorne, 2021 ; Deneu et al, 2021 ; Anand et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As any ML-derived product, our predictions would benefit from having more and better quality data on tree species, in particular those that come from NFI plots: it is now crucial to have such data freely available to monitor processes such as species compositional changes, niche shifts, forest regrowth and degradation, as recently stated by Nabuurs et al (2022) . Exploring more sophisticated and different ML algorithms such as Deep Learning (DL) techniques ( Lakshminarayanan, Pritzel & Blundell, 2016 ) for our ensemble framework is also another area of improvement given the wide variety of applications these methods possess and the results obtained in comparison with other conventional ML algorithms ( Choe, Chi & Thorne, 2021 ; Deneu et al, 2021 ; Anand et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As any ML-derived product, our predictions would benefit from having more and better quality data on tree species, in particular those that come from NFI plots: it is now crucial to have such data freely available to monitor processes such as species compositional changes, niche shifts, forest regrowth and degradation, as recently stated by Nabuurs et al (2022). Exploring more sophisticated and different ML algorithms such as Deep Learning (DL) techniques (Lakshminarayanan et al, 2016) to our ensemble framework is also another area of improvement given the wide variety of applications these methods possess and the results obtained in comparison with other conventional ML algorithms (Choe et al, 2021;Deneu et al, 2021;Anand et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our results extend the findings from previous studies (Botella et al . 2018; Benkendorf & Hawkins 2020; Anand et al . 2021; Capinha et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Capinha et al (2021) demonstrated that some deep learning architectures allow using spatial time series data directly as predictors of ecological phenomena, hence overcoming the need of using temporally unvarying, pre-assembled, predictors sets. In addition, SDM practitioners have been also turning to deep learning (Anand et al . 2021), but as an alternative algorithms to use in conventional workflows with static predictors (e.g., Botella et al .…”
Section: Introductionmentioning
confidence: 99%